Global Processing Makes People Happier Than Local Processing - Ji, Li-Jun; Yap, Suhui; Best, Michael W.; McGeorge, Kayla (Frontiers in Psychology, 2019)
Past research demonstrates that mood can influence level of perceptual processing (global vs. local). The present research shows that level of perceptual processing can influence mood as well. In four studies, we manipulated people’s level of perceptual processing using a Navon letter task (Study 1), landscape scenery (Study 2), and Google Maps Street View images (Studies 3 and 4). Results from these studies and a meta-analysis support the conclusion that global processing results in higher happiness than local processing. In conjunction with previous findings that mood affects level of cognitive processing, these results suggest that the link between level of processing and mood may be reciprocal and bidirectional.